Investigating the User Experience of AI Chatbots in Delivering Mental Health Support to Athletes - Maisarah, Syarifah; Lee , Angel; Azzahranisa , Nafesa (Health Nexus, 2025)
This study aimed to explore how athletes experience and perceive the use of artificial intelligence (AI) chatbots as a source of mental health support, focusing on effectiveness, usability, emotional connection, and limitations. A qualitative exploratory design was employed. Twenty-two athletes from diverse sports disciplines in Malaysia were recruited using purposive sampling. Data were collected through semi-structured, in-depth interviews conducted online to allow flexible participation and confidentiality. The sample size was guided by theoretical saturation, reached when no new themes emerged. All interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. NVivo 14 software supported systematic coding, with open, axial, and selective coding applied iteratively to generate categories and subthemes. Rigor and trustworthiness were ensured through member checking, peer debriefing, and an audit trail. Four main themes emerged: perceived effectiveness of AI chatbots, usability and interaction experience, emotional and relational dynamics, and barriers and limitations. Athletes reported improved mental well-being, reduced competition-related anxiety, and personalized coping strategies. They valued intuitive interfaces, empathetic conversational style, and privacy features, which encouraged engagement and disclosure. Chatbots fostered a sense of trust and emotional validation but sometimes lacked depth and produced repetitive responses. Barriers included occasional technical instability, insufficient long-term personalization, cultural mismatches, and data security concerns. Despite these limitations, participants viewed chatbots as valuable early support tools and stigma-free entry points to mental health care. AI chatbots show promise in enhancing access to psychological support for athletes, offering discreet, immediate, and personalized assistance. However, improving cultural sensitivity, personalization, technical reliability, and data transparency is crucial for sustained engagement and safety in sports mental health contexts.